The frequency of Candida species in onychomycosis - Dorko, E; Jautová, J; Tkáciková, L; Wantrubová, A (Folia microbiologica, 2002)
Mycological investigation of 108 nail specimens taken from a total of 41 patients examined over three years included direct microscopy and repeated cultures. A higher incidence of onychomycosis of the fingernails (75%) was observed in women while afflictions of the toenails (71%) prevailed in men. The highest prevalence of onychomycosis was found in patients between 50 and 70 years of age. Candida albicans was the dominant organism causing onychomycosis (prevalence rate 60.9%), followed by C. parapsilosis (19.6%), C. tropicalis (9.8), C. krusei (4.9), C. guilliermondii and C. zeylanoides (2.4% each).
Keywords: Female; lidé středního věku; dermatózy nohy (od hlezna dolů); mužské pohlaví; Retrospective Studies; retrospektivní studie; Humans; dospělí; Foot Dermatoses; Candida albicans; Candidiasis; dermatózy ruky; lidé; Middle Aged; senioři; Hand Dermatoses; ženské pohlaví; kandidóza; Onychomycosis; onychomykóza; Aged; Adult; Male